Ali formalni in strokovni dokumenti s področja šolstva spodbujajo participacijo učencev? - Kodele, Tadeja (Sodobna pedagogika, 2015)
In the last two decades, children%s participation has been the subject of numerous discussions and a great deal of research. Changes in the relationships between adults and children became particularly salient following the adoption of the Convention on the Rights of the Child (1989), in which children were encouraged to express their opinions and adults were encouraged to pay more attention to these opinions. Various definitions of participation show that the level of children's participation is understood on a scale ranging from non-participation - the level at which children are not heard or taken into account - to the level at which children are acknowledged as active and competent participants who have the power to influence their own lives. This article presents answers concerning the nature of the concept of participation in the formal and professional documents that define professional work in Slovenian primary schools. Theoretical analysis has shown that pupils' participation in matters that are relevant to them can be defined from three perspectives: the opportunity to express their own opinion, the opportunity to choose and the practice of staying informed. However, the definitions of participation found in most of the analysed documents do not relate to genuine participation (i.e., they fail to emphasise children's involvement in all phases: that is, not only facilitating children's expression of opinions, but also accepting these opinions as significant and equivalent to adult opinions in decision-making as well as taking responsibility for them). Therefore, participation is largely left to adults' perceptions concerning the possibilities for its realisation.
Keywords: participation; učenec; pupil; soodločanje; vzgoja in izobraževanje; šolstvo; school; strokovni dokumenti; učenci; participacija; prevzemanje odgovornosti; osnovne šole